The musical life of Gustav Mole - Meyrick, Kathryn ([S.l.] : Childs Play, 1989)
Gustav Mole is born into a musical family that sing and play musical games as they grow up. He serenades his future wife with a violin and after they marry he becomes a composer.
5.1
K-3
Keywords: Music -- Fiction; Violin -- Fiction; Moles (Animals) -- Fiction; Music -- Fiction; Violins -- Fiction; Moles (Animals) -- Fiction